The Influence of Key Component Characteristic on the Resistance to Progressive Collapse of Composite Joint With the Concrete-Filled Steel Tubular Column and Steel Beam With Through Bolt-Extended Endplate - Shi, Yan-Li; Zheng, Long; Wang, Wen-Da (Frontiers in Materials, 2019)
Finite element (FE) analysis of composite joint with the concrete-filled steel tubular (CFST) column and steel beam with through bolt-extended endplate was carried out in the case of progressive collapse in this paper. The reasonable constitutive model of steel plate, through bolt and core concrete materials under large deformation were selected, and the comprehensive fracture criterion and damage evolution path of ductile damage, shear damage and mixed damage modes based on stress triaxiality were considered in the steel constitutive structure, respectively. The accuracy of modeling method and material constitutive was verified by the comparison of the overall deformation processes, failure modes and resistances of joints with experimental results and FE results. A typical composite joint with the CFST column and steel beam with through bolt-extended endplate was designed, and four joints were derived for comparison by adjusting the diameter of through bolt and the thickness of extended endplate. The FE models of these five joints were established to investigate failure modes and resistance mechanisms by using ABAQUS/Explicit module. The results show that the failure modes of composite joint with the CFST column and steel beam with through bolt-extended endplate can be divided into three types: steel beam and through bolts failure, through bolts failure, and steel beam failure. The different strengths and weaknesses between the through bolt, extended endplate and steel beam affect the progressive collapse resistance of joint directly. With the increase of the diameter of through bolt and the thickness of extended endplate, the failure mode of joint gradually turns from through bolt failure to steel beam failure, and the resistance and ductility of joint are enhanced, the anti-progressive collapse ability of composite joint with CFST column and steel beam with through bolt-extended endplate increases.